Evaluation of the potential therapeutic effect of africanized honeybee venom (Apis mellifera Linnaeus) on levodopa-induced dyskinesias in mice - CAMILA G. DANTAS; ADRIANO A.S. ARAÚJO; RICARDO LUIZ C. DE ALBUQUERQUE JUNIOR; EDNA A.F. CÂNDIDO; MARGARETE Z. GOMES; LUIZ P. DA COSTA (Anais da Academia Brasileira de Ciências)
Abstract Levodopa-induced dyskinesia (LID) is a complication in patients with Parkinson’s disease and undergoing long-term levodopa replacement therapy. This study evaluated the the potential therapeutic effect of Africanized honey bee venom (Apis mellifera L.) on LID in mice. Prior to bee venom (BV) or amantadine treatment, mice received medial forebrain bundle microinjections of 6-hydroxydopamine or ascorbate saline. The animals received dose of levodopa (6mg.Kg-1 for 5 days and 12mg.Kg-1 for 10 days) combined with a dose of 12 mg.Kg-1 of benserazide, for 15 days. Amantadine (40mg.Kg-1) or BV were administered at different dosages (0.1; 0.5 or 1mg.Kg−1) once every 2 days, starting from the last day of levodopa administration, for 2 weeks. The evaluation of abnormal involuntary movements, cylinder test, open field, rotational behavior and wire suspension were done on the day following the last administration of treatment. Was carried the histopathological analysis. The chemical composition of BV was also assessed, identifying the highest concentrations of apamin, phospholipase A2 and melittin and the antioxidant activity. Treatment with BV at a dose of 0.1mg.kg-1 reduced apomorphine-induced rotations, increased the number of contralateral contacts to the lesion, and increased grip strength, restoring motor control impaired by LIDs, indicating potential therapeutic efficacy.